Moving towards a core measures set for patient safety in perioperative care - Dinis-Teixeira, J. P. (2024)
UPDATE NOTICE: Correction: Moving towards a core measures set for patient safety in perioperative care: an e-Delphi consensus study (PLoS One. 2024;19(10):e0311896). PLoS One. 2025;20(1):e0317063. Doi: 10.1371/journal.pone.0317063. Funding Information: The work underlying this manuscript is encompassed in the European project SAFEST (Improving quality and patient SAFEty in surgical care through STandardisation and harmonisation of perioperative care in Europe). This project receives funding from the European Union\u2019s Horizon Europe research and innovation programme under grant agreement No 101057825. Link: https://cordis.europa.eu/project/ id/101057825 The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. The authors would like to commend the SAFEST consortium members for their contribution: Daniel Arnal-Velasco, Joaquim Baneres, Ashish Bartakke, Hiske Calsbeek, Genis Carrasco, Pedro Casaca-Carvalho, Edoardo De Robertis, Yvette Emond, Neus Fabregas, Javier Garc\u00EDa-Silva, Pascal Garel, Oliver Groene, Anita Heideveld-Chevalking, Mari Kangasniemi, Janne Kommusaar, Kaja Kristensen, Andreia Leite, Irene Leon, Ismael Mart\u00EDnez-Nicol\u00E1s, David Marx, Marie Nabbe, Ana Beatriz Nunes, Carola Orrego, Kaja Polluste, Janne P\u00FChvel, Eva Romero-Garcia, Yolanda Sanduende-Otero, Willemijn Sch\u00E4fer, Caroline Schlinkert, Ayshe Seyfulayeva, Victor Soria-Aledo, Paulo Sousa, Joel Starkopf, Rosa Sunol, Helena Vall, Claudia Valli, Nina van der Schoot, Lilian Van Tuyl, Frantisek Vlcek, Marieke Voshaar, Cordula Wagner, Sophie Wang, Adam \u017Daludek, and Sandro Zamarian. The authors would also like to acknowledge the SAFEST Scientific Advisory Group members for contributing to this study: Aamer Ahmed, Fragkiskos Angelis, Catarina Baptista, Metaxia Bareka, Kateryna Bielka, Mercedes Bilbao, Federico Bilotta, Elvira Bisbe, Dialina Brilhante, Pedro Carrascal, Pedro Delgado, Zsuzsanna Farkas-Pall, Loredana Gigli, Helen Haskell, Arvid Steinar Haugen, Jan Hofland, Beverley Hunt, Ib Jammer, Janek Kapper, Natasa Kovac, Susana Lorenzo, Rui Malheiro, Xose Manuel Meijome, Jannicke Mellin-Olsen, Margaret Murphy, Maria Ntalouka, Marta Dora Ornelas, Margarita Ovsepyan, Maria Papadakaki, Danica Rotar Pavlic, Julien Picard, Marek Pietruszka, Benedikt Preckel, Finn Radktke, Jos\u00E9 Manuel Rodr\u00EDguez, Narimantas Evaldas Samalavicius, Pedro Vieira dos Santos, Ed Schoemaker, Kawaldip Sehmi, Henri\u00EBtte Smid-Nanninga, Joel Starkopf, John Tansley, Francesco Venneri, Matthias Weigl, and Argyro Zoumprouli. Publisher Copyright: Copyright: © 2024 Dinis-Teixeira et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.